Análise dos métodos não invasivos de avaliação hepática em pacientes portadores de hepatite c crônica no ambulatório de hepatologia da Universidade Estadual do Pará, entre os anos de 2014 e 2016 - SANTOS, Marcos Vinicios Rodrigues dos (2019)
Chronic hepatic diseases, especially the chronic hepatitis C, may go on in a silent manner for years until they manifest with complications such as cirrhosis, portal hypertension and hepatocarcinoma. Whats make it is essential to make a diagnosis before these manifestations. Noninvasive methods for evaluating fibrosis are alternatives to hepatic biopsy, which allow assessment of liver fibrosis at any stage, especially in the more advanced stages, these alternative methods are not a operator-dependent, they has few contraindications and they presents no risk to the patient. The present study is an observational and cross-sectional. This article use charts of patients treated at a one Belém hepatology outpatient clinic. The medical records should include liver biopsy, transient elastography, and laboratory tests to allow the calculation of APRI and FIB 4. In the statistical analysis, the qualitative variables were characterized according to their absolute and relative frequencies, using the Shapiro-Will test for qualitative and quantitative variables. The KruskalWallis test was used to evaluate the relationship between noninvasive tests and the Metavir characterization. For the analysis of sensitivity, specificity, accuracy and other inference tests were made hepatic biopsy used as the gold standard diagnostic test. In addition, new points and cut second ROC curve and the area under the curve were evaluated. The genotype 1 was the most prevalent, followed by 3. There was a balance in the stages, according to the Metavir classification of the studied group. The total of 21 patients had advanced degrees of hepatic fibrosis (F3 and F4). From 97 charts analyzed, 40 was included following the criterias. The mean age was 58.25 (SD = 11.48). The fibroscan demonstrated 100% sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV), with statistical significance (p <0.001), unlike FIB-4 and APRI, which did not present significance values. Fibroscan obtained 1,000 in the area under the curve, while FIB-4 and APRI resulted in 0.701 and 0.751, respectively. The Fibroscan accuracy was 100%. The prevalence of viral genotype 1 is not unique to this region. It follows a world standard, just as second is genotype 3, followed by 2. The prevalence of viral genotype 1 is not unique to this region. It follows a worldwide pattern, as in the second place is genotype 3, followed by 2. The distribution of patients did not show a significant predominance of any group in this or other verified works. Fibroscan, through a study of 349 patients with various chronic liver diseases, presented AUROC values of 0.87 for severe fibrosis (F3 / F4) and 0.90 for hepatic cirrhosis. It was shown to be an effective alternative in the staging of liver fibrosis and having a good correlation with the Metavir index. In addition, it has an excellent sensitivity and specificity. Due to the different cut-off values proposed between the studies, sensitivity and specificity. They had great variations for FIB-4 and APRI, where all cut-off points were smaller than those defined in national protocols, requiring further discussion about the possibility of reduce these positions so that it is safe to choose these methods over biopsy.